Kindergarten Strategy in Online Learning Amid the Covid-19 Pendemic At Aisyiyah 3 Randegan - Loetfi Yanti Rosdiana; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this study is to describe the strategies that Kindergartens (TK) can use during a pandemic so that activities can run optimally. This research describes things that Kindergarten can do, such as learning activities, collaboration with parents, methods and strategies that use descriptive qualitative research methods. A qualitative approach is a research process to understand social or human problems by analyzing words to create complex and comprehensive, and reporting information obtained from sources in the natural environment. This approach also aims to find, discover, describe, and explain the quality or features of social influence that cannot be explained, measured, or described quantitatively. Based on the research, the strategies applied in schools are: (1) aspects of physical-motor development, especially for fine motor development, in the form of paper for drawing, announcing, matching, cutting, stamping, pasting, collage, maze, forming using playdough whose recipe has been written. teachers for parents, (2) Aspects of cognitive development to develop the ability to think logically, think symbolically, and solve problems. (3) Aspects of religious and moral values, in the form of appeals to parents so that children are accustomed to worship under the guidance of parents, reading Iqro ', memorizing and reciting daily prayers, short letters and Asmaul Husna. (4) Social-emotional aspects, so that children have self-awareness, responsibility to themselves and others, and are accustomed to having pro-social behavior.